Talk FK Grant application PDU Grant Made in UMP Grant and Matching Grant - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 30 June 2021 - A talk on grant application (PDU Grant, Made in UMP Grant and Matching Grant) to all academic staff of FK was held virtually.